1991
DOI: 10.1111/j.1744-7348.1991.tb04883.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nitrogen and fungicide on cereal aphid population development and the consequences for the aphid‐yield relationship in winter wheat

Abstract: In a field trial, done over two seasons, nitrogen and fungicide inputs to winter wheat were varied to obtain a range of yields to study the effects on aphid population development and the aphid-yield loss relationship. In the first year, the maximum density of Metopolophium dirhodum and total aphid index were significantly higher in the plots receiving the largest amount of nitrogen but there were few other consistent effects on aphid population development. In the second year there were no significant effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Population Trends. The abundance of each aphid species varied according to year and locality in Nova Scotia, a situation similar to that observed by Robert and Rouze-Jean (1975) in France and Zhou and Carter (1991) and Vickerman (1977) in England. Vickerman (1977) concluded that higher numbers of aphids on winter cereals in midsummer correlated with cool, damp weather conditions in March and April in England.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Population Trends. The abundance of each aphid species varied according to year and locality in Nova Scotia, a situation similar to that observed by Robert and Rouze-Jean (1975) in France and Zhou and Carter (1991) and Vickerman (1977) in England. Vickerman (1977) concluded that higher numbers of aphids on winter cereals in midsummer correlated with cool, damp weather conditions in March and April in England.…”
Section: Discussionsupporting
confidence: 83%
“…Hinz et al (1976) and Latteur (1976) found that chlormequat chloride slightly inhibited the development of S. avenue and R. padi, both in the field and under laboratory conditions. Zhou and Carter (1991) found no consistent effects on aphid populations in plots treated with five different fungicides. Although several herbicides increased mortality of R. padi and C. septempunctata in laboratory studies, the timing of herbicide application at pre-plant or early pre-emergence would reduce the field impact of these IPM components on aphid and predator populations.…”
Section: Discussionmentioning
confidence: 83%
“…Farmers could therefore improve their collard yields by adapting an IPM scheme, which holds potential for high yields and abridged aphid damage. The vegetative growth of collards and other brassicas is usually boosted with high nitrogen (Scaife & Turner, 1985; Scaife & Bar‐Yosef, 1995), but the increase in soil N also increases infestation of collards by B. brassicae (Mattson, 1980; Koritas & Garsed, 1985; Zhou & Carter, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…At the start of the experiment, source colonies consisted of 50–60 aphids, of which the majority was in the second to fourth instar and thus pre‐reproductive. This population distribution and the short duration of the experiment avoided confounding effects of host quality on the performance of the aphids (Zhou & Carter, 1991; Duffield et al ., 1997) with its effects on dispersal. Target trees were generated by planting 40 similar‐sized cuttings of the hybrid willow S. viminalis ‘Jorr’ in 1‐litre pots containing a 1:1:1 mixture of sand : grit : peat.…”
Section: Methodsmentioning
confidence: 99%